2020
DOI: 10.1029/2020ja028238
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the Long‐Duration Daytime TEC Enhancements at Different Longitudinal Sectors During the August 2018 Geomagnetic Storm

Abstract: In this study, the ionospheric responses in the Asian-Australian, American, and African sectors during the August 2018 geomagnetic storm were investigated based on the Beidou geostationary orbit (GEO) satellite and Massachusetts Institute of Technology (MIT) Madrigal total electron contents (TECs), combined with measurements from ionosondes, magnetometers, and Global Ultraviolet Imager (GUVI). The middle-and low-latitude TECs were dominated by positive responses over the three longitudinal sectors during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 63 publications
(144 reference statements)
6
16
0
Order By: Relevance
“…They thought that this ionospheric density enhancement is possibly attributed to the lower atmospheric forcing. Similar features are also reported during the recovery phase of the August 2018 storm and the March 2015 storm by Li et al (2020) and Kuai et al (2016), respectively. Furthermore, Liu et al (2008) analyzed ionospheric pre-storm enhancements in NmF2 and total electron content (TEC) at low latitudes and suggested that a possible cause is the zonal electric field unrelated to geomagnetic storms.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…They thought that this ionospheric density enhancement is possibly attributed to the lower atmospheric forcing. Similar features are also reported during the recovery phase of the August 2018 storm and the March 2015 storm by Li et al (2020) and Kuai et al (2016), respectively. Furthermore, Liu et al (2008) analyzed ionospheric pre-storm enhancements in NmF2 and total electron content (TEC) at low latitudes and suggested that a possible cause is the zonal electric field unrelated to geomagnetic storms.…”
supporting
confidence: 82%
“…the ionosphere and thermosphere could react to geomagnetic disturbance differently due to the different solar EUV energy input. The research on the ionosphere variations during the storm or quiet time in solar minimum has also been ongoing (e.g., Cai, Burns, Wang, Coster, et al, 2020;Klenzing et al, 2013;Laskar et al, 2020;Li et al, 2020). However, some ionospheric variations/phenomena during geomagnetic storms are possibly not attributed to the energy injections from the solar wind and magnetosphere.…”
mentioning
confidence: 99%
“…For the same storm event, Xiong et al (2019) further found that the dayside ionosphere at low-and equatorial-latitudes exhibited prominent positive and negative responses in the Asian and American longitudinal sectors, respectively, which agrees very well with the Equatorial Electrojet (EEJ) variations observed with two ground-based magnetometers located at Huancayo in Peru and Davao in the Philippines. Similar long-lasting daytime TEC enhancements at low and equatorial latitudes were observed in another storm recovery phase on 27-30 August 2018 (Li et al, 2020), but the opposite ionospheric response in Asian and American sectors as reported by Xiong et al (2019) was not observed.…”
Section: Introductionsupporting
confidence: 79%
“…For the storm in August 2018, although Li et al (2020) found in general a positive ionospheric response in the Asian sector during the storm recovery phase, different TEC perturbations were observed for the stations at different latitudes, with a much weaker positive response (or even negative) for the northern stations, e.g., the BBKD and HKWS (see their Fig. 3).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation